Employment Opportunities and Benefits for People with Down Syndrome in Malaysia: A Qualitative Research - Abg Safuan, Adenan; Md Mizanur, Rahman; Sharifa Ezat, Wan Puteh; Razitasham, Safii; Rosalia, Saimon; Chen, Yoke Yong; Ting, Chuong Hock (Stockholm University Press, 2024)
Background: Despite the importance of employment on individual well-being, the literature on the positive impact of work participation, speciﬁcally for individuals with Down syndrome, is scant.Aim: We conducted in-depth interviews to explore how people with Down syndrome perceive employment beneﬁts in Malaysia.Method: Forty-ﬁve participants were interviewed, including six individuals with Down syndrome, ten family members, six employers and co-workers, 22 community members, and a policy maker.Result: Three themes emerged from reﬂexive thematic analysis: (1) personal growth, (2) employer incentives, and (3) improving social acceptance.Conclusion: The ﬁndings emphasise that fostering a positive attitude towards the employment of individuals with Down syndrome would beneﬁt them and contribute to society. Relevant bodies could utilise the ﬁndings to develop effective employment policies for the community